Efficacy of Percutaneous Image-Guided Rupture of Lumbar Facet Cysts: A Retrospective Study - Yohei Ishihara; Masutaro Morishita; Koji Kanzaki (Advances in Orthopedics)
Background. Percutaneous rupture of lumbar facet cysts (LFC) is the only nonsurgical treatment which is effective in directly reducing cysts. However, this is not yet a common procedure, and its effectiveness, including the associated complications, remains unclear. Therefore, this study aimed to evaluate the clinical outcomes of percutaneous rupture for LFC and elucidate whether this minimally invasive procedure could become an alternative to surgeries for cases resistant to conservative treatments. Methods. This study investigated 57 symptomatic patients with LFC for whom conservative treatments were ineffective and underwent percutaneous rupture of the LFC. All patients were followed up for >2 years posttreatment. Clinical evaluations (visual analogue scale (VAS) and recovery rate calculated using the Japanese Orthopedic Association (JOA) scores) and radiographic evaluations (size of LFC based on magnetic resonance imaging (MRI)) were performed from pretreatment to the final follow-up examination. Results. Successful LFC rupture, without hospitalization and general anesthesia, was achieved in 48 patients. No severe complications occurred during treatment through the last observation. Satisfactory clinical results with significant improvements in the VAS and JOA scores were obtained (VAS: pre/posttreatment: 80.7 mm/11.2 mm, JOA: pre/posttreatment: 15.6 points/26.7 points, and recovery rate: 82.3%). A significant reduction in the LFC was also observed in all cases based on the posttreatment MRI findings. No successful rupture cases required subsequent surgical treatments, although four cases of LFC recurrence required additional percutaneous rupture treatment. Conclusions. Percutaneous rupture for LFC is not only a safe and minimally invasive procedure without any severe complications or requirements for hospitalization and general anesthesia but also a beneficial procedure that can eliminate the need for surgery in cases resistant to conservative treatments.